Pengaruh Perceived Ease of Use, Perceived Usefulness, dan Trust Terhadap Kepuasan Konsumen Pengguna Dompet Digital Ovo di Kota Surabaya. - Indah Respati Kusumasari; Leli Hutahaean (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
OVO is a payment service provider application designed to simplify cashless transactions and provide access to additional digital financial products and services through partnerships with selected collaborators. This study aims to evaluate how Perceived Ease of Use, Perceived Usefulness, and Trust affect user satisfaction with the OVO Digital Wallet, both collectively and individually. The research involved a sample of 100 respondents selected from an unspecified population, with data analyzed using SPSS. The findings indicate that Perceived Ease of Use, Perceived Usefulness, and Trust together influence customer satisfaction. While Perceived Ease of Use and Perceived Usefulness partially impact customer satisfaction, Trust does not show a significant partial influence.